Inclusive Teaching Skills and Student Engagement in Physical Education - Bertills, Karin; Granlund, Mats; Augustine, Lilly (Frontiers in Education, 2019)
Including students with disabilities in school-based Physical Education (PE) is common practice. However, little is known about students’ engagement and interaction in this environment and how it is related to PE teaching skills. Student engagement and interaction patterns were therefore observed. A multiple time-sampling method was used to perform observations of individual, contextual and environmental aspects of student engagement in school-based PE lessons. Three groups of students, aged 14, (n=94) with: 1. Disabilities (n=23), 2. Low grades (n=27), and 3. High grades (n=44) were compared. Students, independently of group, show relatively high engagement in PE. The observed frequency of linking lesson content to PE syllabus in combination with using a vibrant affective tone when instructing was used as an indicator of high-/low-level teaching skills. Higher student engagement was found in environments with high-level PE teaching skills, which included more whole group contexts, a higher frequency of student-teacher communicative proximity and more instructions. Students with disabilities and with low grades were more often observed in whole group contexts, students with high grades in small group contexts. The primary type of support provided to students with disabilities in PE seems to consist of communicative proximity to the teacher. They were more often observed to be close to the teacher. Our results suggest that proximity to the teacher may serve as an indicator of inclusive teaching. In high-level teaching, teachers were more frequently in communicative proximity to all students, which facilitates learning. In high-level teaching environments, lessons were also more academically focused, and technical device and music were used for teaching purposes. More complex lesson content requires more instructions and our result show that despite more instructions students in general were more on-task. Implied from our observations is that lesson complexity, the structuring of whole/small group contexts, teacher proximity, and student engagement are aspects to consider when studying school-based PE. More instructions, closer communicative proximity and higher student engagement in high-level teaching provide students with more learning opportunities and facilitate feed-back and feed-forward, and individual support to students with disabilities.